(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
Effective study habits are crucial for achieving academic success, as they foster a conducive learning environment and enhance information retention. This paper explores various strategies that contribute to effective studying and some barriers which cause ineffective learning strategies. Emphasizing the importance of goal setting and self-assessment, the study highlights how tailored approaches can cater to individual learning styles. By synthesizing current research and practical applications, this work aims to provide students with actionable insights to optimize their study practices, ultimately leading to improved academic performance and greater confidence in their educational pursuits.